Pengaruh Brand Ambassador, Online Costumer Review, Dan Kuailtas Produk Terhadap Keputusan Pembelian Di Shopee (Studi Kasus Pada Mahasiswa Prodi Manajemen Fakultas Ekonomi Dan Bisnis Unisma) - Hariyanto, Setyo; Wahono, Budi; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Purchasing decision is a stage of the process before post-purchase behavior occurs where previously consumers have been faced with several alternative choices so that consumers will take action to buy a product based on predetermined choices. Before consumers make a purchase decision for a product or service, there are several alternative options that can influence the purchase, such as brand ambassadors, online customer reviews, and product quality on purchasing decisions. The object of this research is shopee because of the many product purchases made at shopee. The population in this study is shopee users in management study program students Class of 2020 Faculty of Economics and Business Unisma, the sample of this study is 82 management study program students, Sampling using Non-probability Sampling technique with Purposive Sampling technique, the type of data used is primary data and uses questionnaires as a medium for collecting data. The results of the analysis that are rigid using SPSS show that: simultaneously online customer review brand ambassadors and product quality have a positive and significant influence on purchasing decisions, brand ambassadors have a positive and significant influence on purchasing decisions, online customer reviews have a positive and significant effect on purchasing decisions, and product quality has a positive and significant influence on purchasing decisions. This research is expected to provide knowledge and be a reference in future researchers Keywords: Brand Ambassador, Online Customer Review, Product Quality, and Purchasing Decision